Organization development and change - "Cummings, Thomas G." (Australia, 2005)
Market-leading Organization Development and Change blends theory, concepts and applications in a comprehensive and clear presentation. The authors work from a strong theoretical foothold and apply behavioral science knowledge to the development of organizational structures, strategies, and processes.
Keywords: Organizational change